INFLUENCERS AS DIGITAL LABOR IN LOCAL TOURISM DEVELOPMENT - Candra Yudha Satriya; Agus Triyono; Nadia Itona Siregar; Anita Amaliyah; Indrayani, Heni (Jurnal Netnografi Komunikasi, 2025)
The tourism sector is a priority driving the regional economy. One effort to build tourism is through the popularity of influencers who can be an alternative used indirectly to re-promote regional tourist destinations. Influencers actively utilize digital media as well-known as digital workers. This research explores the phenomenon of social media influencers in relation to digital workers regarding freedom as content creators and content commodification. Therefore, this research aims to describe the phenomenon of Influencers as Digital Workers in Indonesian Tourism Development in terms of content creation, content production and freedom in selecting tourism content. The method in this research is a qualitative research method with a phenomenological approach based on the concepts of digital labor, social media influencers and tourism development. Primary data from interviews with six local influencers who are members and ambassadors of the Generasi Pesona Indonesia (GenPI) community. Secondary data was obtained through journals, e-books, books, blogs and informant’s social media. To code the interview manuscript and create the co-manuscript networks, we used atlas.ti . The research results show that the communication process by influencers begins with input including content production competencies, content distribution competencies, interaction competencies, public persona, relationship quality and ability to influence. Then in terms of the role of local influencers as content creators, multiplicators, moderators and protagonists. Meanwhile, the output produced by local influencers is in the form of content, reach, interaction, personalization, peer effect, authenticity and credibility. In addition, the outcome is content distribution on various digital media platforms. Finally, in terms of impact, it includes networking and interaction.